Optimalisasi Hasil pada Ruptur Septal Ventrikel : Strategi Integratif dan Tantangan Modern - Rosyidi, Muhammad Azhar; Anjarwani, Setyasih; Yogibuana, Valerinna (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Acute Myocardial Infarction (AMI) requires immediate management to prevent serious complications, one of which is Ventricular Septal Rupture (VSR). This complication necessitates a multidisciplinary approach due to the complex interaction between ischemic injury, mechanical stress, and inflammatory processes within the heart. Post-AMI VSR leads to a left-to-right shunt, resulting in hemodynamic changes that affect both cardiac function and systemic circulation. Echocardiography serves as the primary modality for assessing the size and location of the rupture, although other imaging modalities are also employed for a more detailed evaluation of hemodynamic alterations. Initial management of post-AMI VSR focuses on hemodynamic stabilization through medical therapy. However, mechanical circulatory support, such as Intra-Aortic Balloon Pump (IABP) or Extracorporeal Membrane Oxygenation (ECMO), is often required in more severe cases. Surgical closure remains the gold standard of treatment, although the optimal timing for surgery is still debated among experts. As an alternative, transcatheter closure using occluder devices can be employed as acute, subacute, or definitive therapy, depending on the patient's condition. The management of post-AMI VSR involves hemodynamic stabilization and a decision between surgical or transcatheter closure, which must take into account the patient's clinical profile and the expertise of the medical team involved.